Macroeconomics, human development and political stability: evidence from OIC countries - Dzihny, Izzatu; Wibowo, Muhammad Ghafur; Ihsan, Akmal (Jurnal Ekonomi & Studi Pembangunan, 2023)
This study aims to examine and analyze the effect of macroeconomic variables on the Human Development Index (HDI) in the Organisation of Islamic Cooperation (OIC) countries with political stability as the moderating variable. The GMM (Generalized Method Moment) dynamic panel and the MRA (Moderated Regression Analysis) will be used for determining the type of moderation needed as analysis techniques. In the first section, the findings state that inflation and unemployment have no effect on HDI, This is due to the fact that inflation and unemployment are very dependent on global economic fluctuation. Meanwhile, trade openness has a significant positive effect on HDI and foreign direct investment has a significant negative effect on HDI. This can add to the evidence that a high level of trade openness can support HDI values in OIC countries. Trade Openness can strengthen the economy, education, and health simultaneously by increasing prosperity through increased demand, supply, and services in numerous sectors. Secondly, the value of the moderator variable (political stability) on the relationship between unemployment and HDI demonstrates that political stability acts as a "Quasi Moderator" which means that political instability can exacerbate the negative influence of unemployment on HDI in OIC countries. This research has implications for the importance of cooperation between OIC countries in various fields, especially in increasing trade, investment, job creation and good governance to support the expansion of human development in OIC nations and to build sustainable prosperity.